Penegakan Hukum Terhadap Pelanggaran Penggunaan Sirene dan Lampu Rotator Oleh Polisi Lalu Lintas Resor Kota Pekanbaru - Hamonangan S., Jamri Tumpak; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Everyone in Indonesia using a motor vechicle to facilitate it’s activities and facilitate the move from one area another. During it’s development, the automotive industry in the world are increasingly sophisticated and equipped with additional features to modify the vehicle, such as sirens and lights rotator. Whereas for the use of sirens and lights rotator already regulated in Pasal 59 paragraph (5) of Law Nomor 22 of 2009 on Road Traffic and Road Transport. The purpose of this thesis are: First to find out enforcement against violations of the use of sirens and light rotator by the Traffic Police Resor Pekanbaru, two to find out the barriers in law enforcement againts violations of the use of sirens and lights rotator by the Traffic Police Resort Pekanbaru, and third to know the efforts made to overcome the barriers in law enforcement againts violations of the use of sirens and lights rotator by the Traffic Police Resort Pekanbaru.This type research used in this research belongs to sociologi research. This research was conducted in the city of Pekanbaru. Data collections techniques are using interviews, questionnaires, and literature study. Population and sample is the parties associated with the overall issue of this study. Analysis of the data used is the qualitative techniques by means of deductive inference.From the research that enforcement against violations of the use of sirens and light rotator by traffic police resort town of Pekanbaru has been done although the results are not optimal. Barriers in law enforcement againts violations of the constraints of law enforcement, facilities and infrastructure constraints, constraints of awarenes and compliance with community law. Efforts made in law enforcement against violations of the use of sirens and lights rotator by traffic police resort Pekanbaru disseminations, legal education to the community, a firm stance of the leadership of the members who impede law enforcement proces.Keywords: Implementation - Law Enforcement - Sirens and Lights Rotator